Teachers’ strategies and challenges in conducting HOTS-based activities in Merdeka Curriculum era - Faradella, Niken Emiria; Wiyaka, Wiyaka; Egar, Ngasbun (Indonesian Journal of Education and Pedagogy, 2024)
This study investigated the approach used by English teachers to promote Higher-Order Thinking Skills (HOTS) during the learning process. The Indonesian government, specifically the Ministry of Education and Culture, has taken the lead in implementing the Merdeka Curriculum, a curriculum designed to prepare students for the 5.0 era of society. The objective of this curriculum is to develop students who have the Profil Pelajar Pancasila, equipping them with the ability to use their knowledge and abilities effectively in practical circumstances. To achieve this, teachers must employ specific methodologies that enhance students' critical thinking abilities. focused on thirteen English senior high school teachers in Pekalongan Regency, with two selected for interviews and observations. Data were collected through a questionnaire, interviews, and direct observation. The data analysis involved quantifying the questionnaire responses, evaluating the open-ended questionnaire responses, and reviewing the transcripts from the interviews and classroom observation notes. Thematic analysis was used to interpret the data from interviews and classroom observation, while coding was employed to extract the transcripts and observation notes. The study revealed that the strategies used by Merdeka Curriculum teachers were project-based learning and open-ended questioning. However, some teachers faced challenges in implementing these strategies in English classes, such as students' skill levels, teachers' expertise, and negative perceptions.